Effect of Dynamic Line Ratings on Optimal Dispatch Considering Uncertainty Costs due to Intermittent Renewable Energy⁎. Issue 28 (2018) - Ngoko, Bonface O.; Sugihara, Hideharu; Funaki, Tsuyoshi
Abstract: Dynamic line ratings (DLRs) provide a more flexible use of power transmission networks by reducing the conservativeness of transmission line loadability constraints. The reduced system congestion due to increased loadability of lines monitored for DLR would allow for more economical generation scheduling. This paper analyses the impact that DLR would have on power dispatch with a specific assessment of the allowable uncertainty levels due to IRE generation in a power network. This is done using a solution of an optimal dispatch problem that includes costs due to uncertainty of IRE sources and DLR of monitored lines. Simulation results carried out on a benchmark test system show that the savings occasioned by reduction in conventional generation costs due to DLR can allow for increasing the uncertainty levels in power networks which would translate to increased use of IRE sources.